Selective adsorption of heterophile polyglycerophosphate antigen from antigen extracts of Streptococcus mutans and other gram-positive bacteria. - Hamada, S (1976)
Hot saline extracts of Streptococcus mutans have been shown to contain antigenic substances which occasionally react nonspecifically with some antisera against whole cells of various serological groups and types of streptococci. Chromatography of the extract of S. mutans strain MT703 (serotype e) on a diethylaminoethyl-Sephadex A-25 column gave two principal antigens. One antigen was eluted without adsorption to the resin and was identified as the serotype-specific polysaccharide. The other antigen, which contained a large quantity of phosphorus, was absorbed to and released from the resin by gradient elution. It was reactive against the antisera specific for polyglycerophosphate (PGP) from group A Streptococcus pyogenes and/or S. mutans strain Ingbritt (type c). The PGP antigen was further purified by gel filtration with Sephadex G-75. Two peaks, PGP-1, and PGP-2, were obtained. Each possessed the same antigenic specificity to anti-PGP serum as shown by immunodiffusion. Chemical analyses revealed that the molar ratio of phosphorus to glycerol in both was about 1:1, although the protein content between the two was significantly different. PGP antigen was found to be widely distributed in hot saline extracts from various gram-positive bacteria, with a few exceptions. However, all gram-negative bacteria examined were free of PGP. The PGP in the hot saline extracts of various gram-positive bacteria possessed an essentially identical antigenic specificity. The addition of diethylaminoethyl-Sephadex A-25 resin to hot saline extracts successfully removed the cross-reacting PGP antigen. After adsorption of the extract from S. mutans, the supernatant contained only type-specific polysaccharide antigen, except type b, in which both type b-specific polysaccharide and PGP antigens were absorbed with the resin. This simple procedure should be useful for the removal of the PGP-type teichoic acid from antigen extracts of bacteria that contain uncharged polysaccharides.